Effect of climate change on surface ozone over North America, Europe, and East Asia. Issue 7 (5th April 2016) - Schnell, Jordan L.; Prather, Michael J.; Josse, Beatrice; Naik, Vaishali; Horowitz, Larry W.; Zeng, Guang; Shindell, Drew T.; Faluvegi, Greg
Abstract: The effect of future climate change on surface ozone over North America, Europe, and East Asia is evaluated using present‐day (2000s) and future (2100s) hourly surface ozone simulated by four global models. Future climate follows RCP8.5, while methane and anthropogenic ozone precursors are fixed at year 2000 levels. Climate change shifts the seasonal surface ozone peak to earlier in the year and increases the amplitude of the annual cycle. Increases in mean summertime and high‐percentile ozone are generally found in polluted environments, while decreases are found in clean environments. We propose that climate change augments the efficiency of precursor emissions to generate surface ozone in polluted regions, thus reducing precursor export to neighboring downwind locations. Even with constant biogenic emissions, climate change causes the largest ozone increases at high percentiles. In most cases, air quality extreme episodes become larger and contain higher ozone levels relative to the rest of the distribution. Key Points: Climate change increases surface ozone in polluted regions and decreases surface ozone in nearby and cleaner regions Surface ozone increases are largest at high percentiles even with constant biogenic emissions Air quality extremes become more hazardous under future climate warming